Planialtimetric and physical-chemical data in florida mangrove diebacks - Marcelo Cancela Lisboa Cohen (PANGAEA, 2024)
Coordinates, orthometric heights, as well as mangrove heights, obtained by the Antenna Catalyst, Electronic Self Leveling Horizontal Rotary Laser, and a ruler. Orthometric and vegetation heights are also shown, obtained by the digital elevation and digital terrain models. Porewater salinities were obtained by a refractometer.
In: Cohen, MCL (2024): Florida mangrove diebacks [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.964591